The Impact of Foot and Mouth Disease on Cow Milk Supply Chain in Bogor - Tanjung, Dahri; Ristianingrum, Anita; Dewi, Intani; Firhani, Liisa; Sayekti, Ayutyas; Lidya, Leni; Machmuddin, Nurlela; Purnamadewi, Yeti Lis; Sebayang, Veralianta; Kuntari, Wien (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2025)
Foot and Mouth Disease (FMD) outbreak in 2022 reportedly led to a significant decrease in cow milk production, resulting in major changes to supply chain. Therefore, this study aims to determine the current supply chain performance of dairy milk at Bogor Dairy Farm Cooperative (BDFC) using Supply Chain Operation Reference (SCOR) metric. A quantitative descriptive method was used, and data were collected through field observation, interviews, and Focus Group Discussions (FGDs). Furthermore, the data were analyzed using SCOR metric. The results showed that the currentsupply chain performance comprised several entities, including cow milk suppliers (152 dairy farmers),cooperative, 3 manufacturers (milk processing industries), and end consumers. The time required by BDFC to distribute cow milk to processing industries was relatively fast (around 2 hours) due to the perishable nature. The calculation of supply chain performance yielded positive results, with SCOR metric achieving perfect order-fulfillment (POF) value of 86.9% andorder fulfillment cycle time (OFCT) of 2 days.Meanwhile, the cost of goods sold (COGS) value was 42.3%, with cash-to-cash cycle time (CTCCT) of 2 days.